Analyzing Land Conversion Rate and Conversion Farmer Household Food Security in Bakalan Village, Pasuruan Regency - Puput Cindy Novianty; Soemarno; Anthon Efani (Jurnal Penelitian Pendidikan IPA, 2025)
The conversion of agricultural land to non-agricultural uses presents significant challenges to food security, environmental sustainability, and economic progress in Bakalan Village. Food security categories for Bakalan Village conversion farmer families are assessed in this study using System Dynamic and Land Conversion Rate Analysis. A causal loop diagram illustrates the complex relationships between land conversion, food availability, affordability, and needs, crucial for understanding food security dynamics. Higher land conversion rates negatively impact food availability, risking local food security. System Dynamic integrates agricultural and non-agricultural income sources to model food affordability, a key food security determinant. Annual iterations capture fluctuations in land use, income, and food indicators, revealing the evolving impact on food security. This research emphasizes the need for sustainable land use practices, incentivizing land preservation, and promoting diversified incomes to ensure food security, environmental resilience, and socio-economic stability in Bakalan Village and similar agricultural communities globally. Adaptive policies informed by such models are essential for addressing these multifaceted challenges effectively.